Acute high-altitude pulmonary edema in Huaraz: an analytical cross-sectional study - Lopez de Guimaraes, Douglas (2022)
Objective: To describe some epidemiological and clinical characteristics of acute high-altitude pulmonary edema (HAPE) observed in a hospital of the highlands of Ancash, located at 3,052 m a.s.l. Materials and methods: A descriptive observational study conducted with 57 patients who attended the emergency service of Hospital Víctor Ramos Guardia – Huaraz between January 1997 and January 2020. All patients fulfilled Lake Louise Criteria and had a chest X-ray. Median and range were used to analyze the information.Results: Male sex accounted for 91.20 %, ascent HAPE 38.61 % and re-ascent HAPE 61.40 %. Out of all patients, 21.10 % had a history of HAPE, 19.33 % developed a previous respiratory infection, 10.53 % had a concomitant disease, 40.42 % had HAPE during the first quarter of the year and 45 % had been 10 days or less at low altitude. Patients’ clinical presentation included dyspnea at rest, pulmonary crackles, tachypnea, tachycardia and abnormal X-ray in 100 %; productive cough in 96.52 %; chest pain in 92.95 %; headache in 56.11 %; cyanosis in 68.41 %; pink sputum in 42.13 %; fever in 21.13 % and leukocytosis in 60.82 %. The median age was 20 years, respiratory rate 36/min, heart rate 124/min, SBP 100 mmHg, DBP 60 mmHg, temperature 37.2 °C, HGB 17.3 g/dl, HCT 53 %, WBC 12,500/mm3, radiographic resolution of the edema in 48 hours. There were no deaths. Conclusions: The factors that influence HAPE and its determinants are altitude, rate of ascent, genetic factors and history of HAPE.